2009
DOI: 10.1111/j.1365-2702.2009.02955.x
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of what factors attract and retain nurses in aged and dementia care

Abstract: A family-friendly, learning environment that values and nurtures its nursing staff, in the same way as nurses are expected to value and care for their patients and residents, is critical in ensuring their retention in dementia and aged care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
109
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(114 citation statements)
references
References 41 publications
4
109
1
Order By: Relevance
“…Literature confirms that there is a shortage of nurses caring for older persons (Chenoweth et al, 2010;Christopher et al, 2015;DSD, 2010;Fedele, 2015).…”
Section: Themes and Sub-themesmentioning
confidence: 88%
See 3 more Smart Citations
“…Literature confirms that there is a shortage of nurses caring for older persons (Chenoweth et al, 2010;Christopher et al, 2015;DSD, 2010;Fedele, 2015).…”
Section: Themes and Sub-themesmentioning
confidence: 88%
“…An increasing shortage of nurses caring for older persons became evident from several reports, while there is an increased need for such care brought about by the ageing population (Chenoweth et al, 2010;Christopher et al, 2015;DSD, 2010;Fedele, 2015;WHO, 2011). According to Jackson et al (2007, p. 1, 7) nurses can be assisted to "survive" and "thrive" in the workplace by building their personal resilience.…”
Section: Research Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…A literature review by Neville and Dickie (2014) reported that most nursing students have a positive attitude towards older adults. Chenoweth, Jeon, Merlyn, and Brodaty (2010) conducted a systematic review and determined successful strategies to recruit and retain nurses in aged care included ongoing supervision, education, training, and teamwork. In comparison with changing student attitudes however, there is limited evidence about the impact of an interprofessional placement in aged care in improving student's readiness to learn interprofessionally.…”
Section: Introductionmentioning
confidence: 99%